PENGARUH WAKTU PERENDAMAN DAN PENAMBAHAN KONSENTRASI NaCl (PPM) TERHADAP LAJU KOROSI BAJA LATERIT - Eka Febriyanti; Amin Suhadi; Johny Wahyuady (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2017)
Most of carbon steel are produced from hematite iron ore. The decreasing of hematite iron ore in Indonesia, encouraged iron and steel company to produced carbon steel from laterite mineral, which has high deposit in Indonesia with high grade iron (50% Fe). One of the application of laterite steel as material rooftop bridge. The objective of this research to observe the influence of NaCl increasing to corrosion rate of carbon steel from laterite iron ore on lake water environment. Chemical composition of laterite steel is adding of element such as Cr and Ni, which classified laterite steel into low alloy steel and may effected corrosion behaviour of these steel. Corrosion rate measurement are conducted by weight loss method, which laterite steel immersed in lake water with time period 48, 72, 120, and 168 hour at NaCl adding 200, 300, and 400 ppm. From weight loss testing shows that  corrosion rate of laterite steel increase about from 2.9 mpy until 3.2 mpy.